Medicinal Plants in Sri Lanka: Geographical distribution and its benefits - Ruzaik, Fareena (Geo Book Publication, 2021)
Medicinal plants have been used traditionally to cure diseases. The knowledge and experience on the usage of medicinal plants were shared from generation to generation. Periodically, the usage of medicinal plants for treatment gradually abandoned with the introduction of the western medicine since the 19th century. Once again, usage of medicinal herbs have become prudential after the United Nation’s Conference on “Human and Environment” in Stockholm in 1972. Green concept especially in the tourism hospitality services has contributed immensely to boost the usage of medicinal plants for treatments, prophylaxis, physiotherapy and preparing synthetic drugs. The book on ‘Medicinal Plants in Sri Lanka’ is a guide for identifying the potential medicinal species available in Sri Lanka. This book contains 294 medicinal plants varieties, its distribution, composition, and benefits, which were organized in the alphabetical order. The descriptions of each plant includes photos, their botanical name and common names (Sinhala & Tamil). This book shall be useful for undergraduate and post-graduate students and consumers, those intend to know about multiple varieties of medicinal plants.
Keywords: Medicinal Plants; Sri Lanka